Toosendanin From Melia Fructus Suppresses Influenza A Virus Infection by Altering Nuclear Localization of Viral Polymerase PA Protein - Jin, Young-Hee; Kwon, Sunoh; Choi, Jang-Gi; Cho, Won-Kyung; Lee, Bonggi; Ma, Jin Yeul (Frontiers in Pharmacology, 2019)
Toosendanin (TSN) is a major bioactive component of Melia Fructus (MF) with anti-inflammatory, anti-botulinum, anti-microbial, and analgesic efficacy. Our previous study demonstrated that MF has anti-influenza A virus activity; however, the contribution of TSN is still unclear. In this study, we found that TSN suppressed influenza A virus infection when administered before or concurrent with the virus, but not after infection. TSN pretreatment inhibited viral hemagglutinin (HA), nucleoprotein (NP), polymerase acidic (PA) protein, and matrix protein 2 (M2) mRNA synthesis as well as NP, PA, M2, and nonstructural protein 1 (NS1) expression, but had no effect on HA or neuraminidase (NA) activity. In addition, TSN induced cytoplasmic location of PA protein disrupting nuclear translocation. Docking simulation suggested that the binding affinity of TSN to PA protein may be stronger than that of a known PA protein inhibitor. Pretreatment with TSN also suppressed the infection-induced phospho-AKT expression but not the host immune response. Oral pretreatment with TSN enhanced the survival of infected mice. These results suggest that TSN inhibits influenza A virus infection at an early stage by altering PA protein nuclear localization. Thus, TSN may be a promising candidate for anti-influenza agent targeting the PA protein of the influenza A virus RNA polymerase complex.